Perlindungan Hukum Bagi Investor Pada Perusahaan Dalam Kasus PT. Apa Tobacco Nusantara Menurut Hukum Kepailitan (Legal Protection For Investors In The Company In The Case Of Pt. Apa Tobacco Nusantara According To Bankruptcy Law) - Aulia, Fara; Nurkhaerani, Ema (Media Hukum Indonesia (MHI), 2025)
This research discusses legal protection for investors in the bankruptcy case of PT Apa Tobacco Nusantara based on the perspective of bankruptcy law in Indonesia. Legal protection for investors is divided into two main forms, namely preventive and repressive, which aim to provide a sense of security, certainty, justice, and restoration of investor rights when a violation or dispute occurs. This study uses a descriptive analysis method with a qualitative approach, aiming to describe in depth the characteristics of the bankruptcy phenomenon and the legal protection applied. The results showed that in the bankruptcy process of PT Apa Tobacco Nusantara, all creditors' rights, including investors who have receivables, are strictly regulated under the Bankruptcy Law and the Postponement of Debt Payment Obligations (UUKPKPU). Bondholder investors have protection as creditors and get payment rights in order of priority, while shareholder investors are in the last position in the distribution of remaining assets after all obligations to other creditors are paid. The Financial Services Authority (OJK) plays an important role in the supervision and protection of investors in the capital market, although the risk of loss remains inherent due to the limitations of the bankruptcy mechanism. This research confirms that the bankruptcy process is complex and requires transparency, judge supervision, and information disclosure so that all investor rights can be optimally protected in accordance with applicable legal provisions.